Sistem Monitoring Lulusan Perguruan Tinggi Dalam Memasuki Dunia Kerja Menggunakan Tracer Study - Harianto, Kusno; Pratiwi, Heny; Suhariyadi, Yonatan (STIKOM Tunas Bangsa Pematangsiantar, 2019)
This research is titled Monitoring System of Higher Education Graduates in Entering the World of Work Using Tracer Study. The problem raised in this study is that the BKK (Bursa Kerja Khusus) STMIK Widya Cipta Dharma Samarinda get information about the performance of STMIK graduate students Widya Cipta Dharma, analyze graduate data to obtain the relevance of the competency of STMIK graduates Widya Cipta Dharma Samarinda, change the old system into a system that new. The purpose of this research is to provide information and reports on the results of tracer study data collection from alumni of STMIK Widya Cipta Dharma Samarinda. Data collection methods used are literature study, field studies. The system development method used is the waterfall method. Informatic System of Alumnus Record Tracer Study Based Website of STMIK Widya Cipta Dharma Samarinda is a computer-based system that was built with the aim of processing the alumnus search to find out the description of the profile, performance, and distribution of work location of the alumnus. Informatic System of Alumnus Record Tracer Study Based Website of STMIK Widya Cipta Dharma Samarinda is expected to help assist the BKK (Bursa Kerja Khusus) in recording alumnus and record the track record of alumnus scattered in serveral areas.